Analyzing teacher salaries using the Post-Secondary Employment Outcomes dataset - Andrew G. Biggs; Jason Richwine (American Enterprise Institute (AEI), 2021)
Studies relying upon household survey data have concluded that public school teachers receive substantially lower salaries than comparably-educated private sector workers. However, any given level of formal educational attainment found in household surveys can encompass a wide range of skills as valued in the labor market. We use a recently developed Census Bureau dataset, the Post-Secondary Employment Outcomes (PSEO), that allows us to analyze annual earnings up to 10 years following completion of a Bachelor's or Master's degree while controlling for both the educational institution attended and the field of study in which the degree was granted. We find that the teacher salary gap appears to be largely a function of higher salaries paid to holders of STEM degrees. Education degree holders receive median salaries that are not substantially different from those received by other non-STEM degree holders graduating from the same institutions.
Keywords: A; 330; College Degrees; Economics; Employment; Teachers